Aromatic secondary amine-functionalized fluorescent NO probes: improved detection sensitivity for NO and potential applications in cancer immunotherapy studies - Huo, Yingying (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
Tumor-associated macrophages (TAMs), constituting up to 50% of the solid tumor mass and commonly having a pro-tumoral M2 phenotype, are closely associated with decreased survival in patients. Based on the highly dynamic properties of macrophages, in recent years the repolarization of TAMs from pro-tumoral M2 phenotype to anti-tumoral M1 phenotype by various strategies has emerged as a promising cancer immunotherapy approach for improving cancer therapy. Herein, we present an aromatic secondary amine-functionalized Bodipy dye 1 and its mitochondria-targetable derivative Mito1 as fluorescent NO probes for discriminating M1 macrophages from M2 macrophages in terms of their difference in inducible NO synthase (iNOS) levels. The two probes possess the unique ability to simultaneously respond to two secondary oxides of NO, i.e., N(2)O(3) and ONOO(–), thus being more sensitive and reliable for reflecting intracellular NO than most of the existing fluorescent NO probes that usually respond to N(2)O(3) only. With 1 as a representative, the discrimination between M1 and M2 macrophages, evaluation of the repolarization of TAMs from pro-tumoral M2 phenotype to anti-tumoral M1 phenotype, and visualization of NO communication during the immune-mediated phagocytosis of cancer cells by M1 macrophages have been realized. These results indicate that our probes should hold great potential for imaging applications in cancer immunotherapy studies and relevant anti-cancer drug screening.